FAMIly Physical Activity, Sedentary behaviour and Sleep (FAMIPASS) study: protocol for a cross-sectional study - Dagmar Sigmundová; Jan Dygrýn; Michal Vorlíček; Kamila Banátová; Jaroslava Voráčová; Erik Sigmund (BMJ Open, 2023)
Introduction The development of children’s healthy and active lifestyles, including habit formation for optimal 24-hour movement behaviour, is associated with their family environment. A whole-family study collecting comprehensive data that can evaluate family lifestyle behaviours in different settings in depth has the potential to provide the evidence-based information needed for national guidelines, for designing interventions and for supporting policy-makers’ decisions.Methods and analysis The FAMIly Physical Activity, Sedentary behaviour and Sleep (FAMIPASS) study is a nationally representative cross-sectional study that will recruit 500 families (with at least 1 child aged between 3 and 8 years) from the urban and rural parts of all three regions of the Czech Republic. To examine the relationship between family environment and children’s healthy development (eg, healthy weight) and children’s active lifestyle behaviour, anthropometric measures, parents’ health-related behaviour (including dietary habits, alcohol and tobacco use, screen time and bedtime rules and 24-hour movement behaviour), socioeconomic data and data about the characteristics of the home and neighbourhood will be collected from parents and children. The 24-hour movement behaviour (eg, sleep, sedentary behaviour and physical activity) will be monitored using wGT3X-BT and GT9X Link ActiGraph accelerometers placed on the non-dominant wrist of the children and their parents for 7 consecutive days. The accelerometers will be set up for each family separately, using the group proximity mode, allowing proximity tagging between devices and establishing the time spent together and parent–child coactivities.Ethics and dissemination The overarching methodological protocol of the FAMIPASS project was approved by the Ethics Committee of the Faculty of Physical Culture, Palacký University Olomouc, Czech Republic (reference number: 25/2021). The results and findings will be reported to: (1) the participating families and (2) school representatives and will be (3) presented at national and international conferences and (4) disseminated via peer-reviewed publications.